Development of E-LKPD Based on Google Sites with PBL Model in Achieving Scientific Literacy on the Human Excretory System Subject for XI Grade Students - Irma Wahyu Lestari; Aloysius Hardoko; Herliani; Yusak Hudiyono; Vandalita Maria M. Rambitan; Elsje Theodora Maasawet (Postgraduate, University of Mataram, 2025)
E-LKPD, an electronic learning activity, shows a good impact on student participation and ability to solve problem and apply learning concepts in some previous studies. The collaborative classroom using the problem-based learning model can be designed creatively, innovatively, and interactively, and used broadly using electronic media such as laptops or smartphones. This study aimed to develop Google Sites-based E-LKPD to create a fun learning process, encourage active participation, and improve the ability of students to solve problems and apply learning concepts in human excretory system material for grade XI. The ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation, was applied in this study. The E-LKPD was then analyzed for its practicness and effectiveness on achieving scientific literacy among biology teachers and XI grade students of SMA Budi Luhur Samarinda on even semester of academic year of 2024/2025. The results showed that the developed E-LKPD had a practiceness level of 87.0% and 91.5% for the students and teachers, respectively, which were categorized as very practical. The effectiveness of achieving scientific literacy was applied using N-Gain analysis, which produced N-Gain score of 0.76 (effective) and 0.49 (ineffective) for the experimental and control classes, respectively. The increase in N-Gain in the experimental class was significant (p < 0.01, two-tailed t-test). These results indicate that E-LKPD based on Google Sites is effective in improving students' scientific literacy of the human excretory system material and is suitable for use in school learning for XI grade students.